(untitled) (The Chittagong University Journal of Science, 2018)
An experiment was carried out to assess the radiological exposure due to the intake of fishes and fish like foods from some common estuary (Karnaphuli River) and Marine (Bay of Bengal) contaminated by Fukushima Reactor Accident, if any, by using gamma spectroscopy. The analysis was done to estimate the radioactivity concentrations due to natural radionuclides namely 238U, 232Th and 40K and artificial radionuclide 137Cs in Karnaphuli estuary and Chittagong city adjoining Bay of Bengal fish and fish-like samples. The activity concentration for 238U in all the samples ranged from 0.10615 ± 0.0000 to 2.4767 ± 0.0005 Bq.kg-1 with the mean of 0.6109 ± 0.0001 Bq.kg-1. The Activity of 232Th ranged from 0.0009 ± 0.0000 to 0.0273 ± 0.0000 Bq.kg-1 with the mean of 0.0074 ± 0.0000 Bq.kg-1. The activity concentration for 40K was found to be in the range from 1.5516 ± 0.0311 to 74.8658 ± 0.2532 Bq.kg-1 with the mean of 24.9533 ± 0.0702 Bq.kg-1. The artificial radionuclide 137Cs was not found in any of the samples. The specific activity values for most of the sample were within the permissible limits. The average effective dose and internal hazard index due to consumption of those fishes and fish-like foods was found to be 0.1 mSv.y-1 and 0.0085 ± 0.0000 mSv.y-1 respectively. The research work showed that the consumers of concerned fishes and fish-like foods of the Chittagong area have no risk of radioactivity ingestion even though no amount of radiation is assumed to be totally safe. The Chittagong Univ. J. Sci. 40(1) : 75-96, 2018